CREATION OF AN AUTONOMOUS LEARNING MODEL TO IMPROVE THE LEARNING OUTCOMES OF PHYSICS FOR HIGH SCHOOL STUDENTS - Jon Darmawan; Abdul Hasan Saragih; Ridwan Abdullah Sani; Putri Mayasari (RADJA PUBLIKA, 2025)
Abtract